Impact of Temporal Macropore Dynamics on Infiltration: Field Experiments and Model Simulations - Reck, A. (2020)
We used the model simulations to check whether biopore dynamics affect infiltration. The observed infiltration patterns revealed variations in both biopore numbers and biopore–matrix interaction. The field‐observed biopore numbers varied over time, mainly in the topsoil, with the largest biopore numbers in spring and the smallest in summer. The number of hydrologically effective biopores in the topsoil seems to determine the number and thereby the fraction of effective biopores in the subsoil. In summer, a strong biopore–matrix interaction was observed. In spring, the dominant process was rapid drainage, whereas in summer and autumn, most of the irrigated water was stored in the examined profiles. The model successfully simulated infiltration patterns for spring, summer, and autumn using temporally different macropore setups. Using a static macropore parameterization the model output deviated from the observed infiltration patterns, which emphasizes the need to consider macropores and their temporal dynamics in soil hydrological modeling.